Deficiency of Kruppel‐like factor KLF4 in mammary tumor cells inhibits tumor growth and pulmonary metastasis and is accompanied by compromised recruitment of myeloid‐derived suppressor cells. Issue 12 (3rd September 2013) - Yu, Fang; Shi, Ying; Wang, Junfeng; Li, Juan; Fan, Daping; Ai, Walden
<x xml:space="preserve">Abstract</x> Increasing evidence indicates that myeloid‐derived suppressor cells (MDSCs) negatively regulate immune responses during tumor progression, inflammation and infection. However, the underlying molecular mechanisms of their development and mobilization remain to be fully delineated. Kruppel‐like factor KLF4 is a transcription factor that has an oncogenic function in breast cancer development, but its function in tumor microenvironment, a critical component for tumorigenesis, has not been examined. By using a spontaneously metastatic 4T1 breast cancer mouse model and an immunodeficient NOD/SCID mouse model, we demonstrated that KLF4 knockdown delayed tumor development and inhibited pulmonary metastasis, which accompanied by decreased accumulation of MDSCs in bone marrow, spleens and primary tumors. Mechanistically, we found that KLF4 knockdown resulted in a significant decrease of circulating GM‐CSF, an important cytokine for MDSC biology. Consistently, recombinant GM‐CSF restored the frequency of MDSCs in purified bone marrow cells incubated with conditioned medium from KLF4 deficient cells. In addition, we identified CXCL5 as a critical mediator to enhance the expression and function of GM‐CSF. Reduced CXCL5 expression by KLF4 knockdown in primary tumors and breast cancer cells was correlated with a decreased GM‐CSF expression in our mouse models. Finally, we found that CXCL5/CXCR2 axis facilitated MDSC migration and that anti‐GM‐CSF antibodies neutralized CXCL5‐induced accumulation of MDSCs. Taken together, our data suggest that KLF4 modulates maintenance of MDSCs in bone marrow by inducing GM‐CSF production via CXCL5 and regulates recruitment of MDSCs into the primary tumors through the CXCL5/CXCR2 axis, both of which contribute to KLF4‐mediated mammary tumor development. © 2013 UICC